Using formative feedback to identify and support first year chemistry students with missing or misconceptions : a Practice Report. - Lawrie, Gwen; Wright, Anthony; Schultz, Madeleine; Dargaville, Timothy; O'Brien, Glennys; Bedford, Simon; Williams, Mark; Tasker, Roy; Dickson, Hayden; Thompson, Christopher (International Journal of the First Year in Higher Education v.4 n.2 p.111-116 https://doi.org/10.5204/intjfyhe.v4i2.179, 2013)
Students entering tertiary studies possess a diverse range of prior experiences in their academic preparation for tertiary chemistry, so academics need tools to enable them to respond to issues in diversity in conceptual models possessed by entering students. Concept inventories can be used to provide formative feedback to help students identify concepts that they need to address to improve construction of subsequent understanding enabling their learning. Modular, formative learning activities that can be administered inside or outside of class in first-year chemistry courses have been developed. These activities address key missing and misconceptions possessed by incoming students. Engagement in these learning activities by students and academics will help shift the culture of diagnostic and formative assessment within the tertiary context and address issues around the secondary/tertiary transition. This diagnostic/intervention framework is currently being trialled across five Australian tertiary institutions encompassing a large heterogeneous sample of students. [Author abstract]